Activity of Polyphenolic Compounds against Candida glabrata - Salazar Aranda, Ricardo; Granados Guzmán, Graciela; Pérez Meseguer, Jonathan; González González, Gloria María; De Torres, Noemi Waksman (2015)
Opportunistic mycoses increase the morbidity and mortality of immuno-compromised patients. Five Candida species have been shown to be responsible for 97% of worldwide cases of invasive candidiasis. Resistance of C. glabrata and C. krusei to azoles has been reported, and new, improved antifungal agents are needed. The current study was designed to evaluatethe activity of various polyphenolic compounds against Candida species. Antifungal activity was evaluated following the M27-A3 protocol of the Clinical and Laboratory Standards Institute, and antioxidant activity was determined using the DPPH assay. Myricetin and baicalein inhibited the growth of all species tested. This effect was strongest against C. glabrata, for which the minimum inhibitory concentration (MIC) value was lower than that of fluconazole. The MIC values against C. glabrata for myricitrin, luteolin, quercetin, 3-hydroxyflavone, and fisetin were similar to that of fluconazole. The antioxidant activity of all compounds was confirmed, and polyphenolic compounds with antioxidant activity had the greatest activity against C. glabrata. The structure and position of their hydroxyl groups appear to influence their activity against C. glabrata.